2015
DOI: 10.1080/21645515.2015.1032488
|View full text |Cite
|
Sign up to set email alerts
|

A correlation of measles specific antibodies and the number of plasmacytoid dendritic cells is observed after measles vaccination in 9 month old infants

Abstract: Measles virus (MeV) represents one of the main causes of death among young children, particularly in developing countries. Upon infection, MeV controls both interferon induction (IFN) and the interferon signaling pathway which results in a severe host immunosuppression that can persists for up to 6 mo after infection. Despite the global biology of MeV infection is well studied, the role of the plasmacytoid dendritic cells (pDCs) during the host innate immune response after measles vaccination remains largely u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…GM-CSF and IL-3 were able to efficiently promote pDC survival (40). A significant and direct correlation between the number of pDCs and the development of protective humoral immune response to measles vaccine at 3 months postvaccination is noteworthy (41).…”
Section: Discussionmentioning
confidence: 88%
“…GM-CSF and IL-3 were able to efficiently promote pDC survival (40). A significant and direct correlation between the number of pDCs and the development of protective humoral immune response to measles vaccine at 3 months postvaccination is noteworthy (41).…”
Section: Discussionmentioning
confidence: 88%
“…This suggests a negative influence of the developing infant immune system on the vaccine response after early vaccination [33]. It is known that infants have fewer and less functional dendritic cells [34], and the number of dendritic cells has been positively correlated with the measles virus–specific antibody response [35]. Second, the neonatal immune system is generally thought to be skewed toward a T-helper type 2 response, because fewer T-helper type 1 cytokines are produced [36].…”
Section: Discussionmentioning
confidence: 99%
“…Also, titers < 120mIU/mL do not produce immunity at all. A more recent work revealed that “the development and magnitude of the adaptive immune response following measles immunization is directly dependent on the number of plasmacytoid dendritic cells of the innate immune response“ [ 20 ]. In 2-dose measles-mumps-rubella (MMR) vaccine coverage, a third dose of MMR vaccine had been demonstrated to be safe and important in fighting and preventing measles outbreak [ 21 ].…”
Section: Discussionmentioning
confidence: 99%